HPTLC METHOD FOR ESTIMATION AND QUANTIFICATION OF β-SITOSTEROL FROM IN-VIVO AND IN-VITRO SAMPLES OF MERREMIA AEGYPTIA AND MERREMIA DISSECTA - JOSHI, RIDHI; MEENA, RISHIKESH; MISHRA, PREETI; PATNI, VIDYA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: A normal-phase high-performance thin-layer chromatography (HPTLC) method has been developed and validated for estimation and quantitation of beta-sitosterol from the methanolic fraction of different plant parts of two medicinally important plants viz. Merremia aegyptia and Merremia dissecta. These plants have been reported to possess antimicrobial, antioxidant, and anti-inflammatory activities. Methods: Chromatographic separation of beta-sitosterol from the methanolic extracts of plant parts of M. aegyptia and M. dissecta was performed on TLC aluminum plates pre-coated with silica gel 60F254 using a suitable mobile phase. The densitometric scanning was done after derivatization at ????-580 nm for ????-sitosterol. Result: Only M. dissecta leaf sample was reported to contain ????-sitosterol (4.6 ng/μl), whereas other samples such as seed, stem, and callus extracts of M. aegyptia and M. dissecta did not showed its presence. Conclusion: The developed HPTLC method is simple, rapid, and precise and can be used for routine analysis and quantification of ????-sitosterol and other useful plant bioactives that are phytopharmaceutically important.